Biblical History and Israel’s Past: The Changing Study of the Bible and History. By Megan Bishop Moore and Brad E. Kelle - Williams, Jenni (The journal of theological studies, 2014)
This book is not an attempt at reconstructing a ‘history of Israel’; indeed the authors wonder whether a comprehensive history of this kind is possible or even desirable. It is rather a survey of the scholarly method in dealing with questions of the history of ancient Israel in recent years. In particular, the book shows how the interaction between the study of the Old Testament and disciplines like archaeology has changed. Although it does reach back further, the discussion of method begins with the schools of Albright and Alt and builds from there. The book is written in a measured, eirenic style which does much to take the unwelcome heat out of the maximalist/minimalist debate with which it engages.